A Comparative Analysis of Gender Recognition Laws - Trinity FLAC; Stafford, Caoimhe (Trinity Free Legal Advice Centre, 2015)
This research project was conducted by Trinity FLAC in association with TENI. It sheds light on discrimination that exists against the trans community in the public, political and legal spheres. It focuses on the current Irish position regarding gender recognition law, while also providing a comparative analysis to Argentina and Denmark.
Keywords: Legal advice; Gender recognition laws; Gender; Ireland; Argentina; Denmark